A Meta-Analysis of the Clinical Efficacy of TCM Decoctions Made from Formulas in the Liuwei Dihuang Wan Categorized Formulas in Treating Diabetic Nephropathy Proteinuria. (26th September 2018) - Gao, Xue; Shang, Jianwei; Liu, Hongfang; Yu, Borui
Abstract : Objective. Diabetic nephropathy (DN) is one of the microvascular complications of diabetes mellitus. Proteinuria is the most important clinical characteristics of DN and an independent risk factor for disease progression of DN; reducing urine protein is the primary target of treatment strategies for DN. Liuwei Dihuang Wan Categorized Formulas (LDWCFs), a group of classic traditional Chinese medicine (TCM) formulas aiming at "kidney -tonifying", have been widely used in the treatment of DN. This study aimed to obtain a comprehensive understanding of the TCM method "kidney-tonifying" in the treatment of DN by conducting a meta-analysis to analyze the clinical efficacy of decoctions made from the LDWCFs in the treatment of DN proteinuria. Methods. CNKI, Wanfang, Weipu, CBM, PubMed, Embase, and the Cochrane Library were searched; 14 studies were included in the meta-analysis. Results . The results showed that the overall efficacy of the LDWCFs in treating DN was significantly better than that of the comparators (OR 2.87, 95% CI 1.98–4.15, P <0.00001). These formulas showed better efficacy than the comparators in reducing 24-hour urinary protein level (MD 0.12, 95% CI 0.06–0.17, P <0.0001) and in reducing urine microalbumin excretion rate (SMD 0.87, 95% CI 0.41–1.32, P <0.0002). No serious adverse reactions were reported. Conclusions . TCM formulas included in the LDWCFs are safe and effective in the treatment of DN proteinuria. These findings suggested that the TCM therapeutic principle of "kidney-tonifying" is a valuable addition to the treatment strategies for DN.